Writing, Dancing and Performing Death Across Late Medieval Europe : Texts and Contexts - Léglu, Catherine; Oosterwijk, Sophie; Ungeheuer, Laurent (Literature and Cultural Studies E-Books Online, Collection 2026., 2026)
Our understanding of the medieval Danse macabre is changing with the recent discoveries of a theatrical script from Savoy, and of a related Castilian poem. This collection of texts from the Burgundian realm, France and Savoy, England, Castile-Aragon and the Empire, also contains critical essays that examine these texts and contexts from the fourteenth to the late fifteenth centuries. This volume re-examines the development and impact of the Danse macabre within broader considerations of performance and poetry that focus on Death as a protagonist. It includes texts never before studied or translated and moves beyond the traditional focus on Paris and London to reassess the wide dissemination of this tradition. The volume complements a collection of studies by the same editors (Oosterwijk, Ungeheuer and Léglu) of the visual tradition across Europe, from Burgundy to Finland, Death and the Danse Macabre in Late Medieval Art: Dissemination and Reception .